THE EFFECT OF CHICKEN MANURE AS ORGANIC MATTER AND NPK FERTILIZER ON GROWTH AND YIELD OF CABBAGE IN ALLUVIAL SOIL - Tanti Hidayah, Nikmatun; Warganda, Warganda; Anggorowati, Dini (Jurnal Sains Pertanian Equator, 2022)
Cabbage Flowers are flower buds in large numbers forming thick and dense circles. Utilization of alluvial soil as a growing medium is faced with low soil fertility, acidic soil pH, low levels of organic matter availability, and lack of nutrient content. The limited carrying capacity of the alluvial soil needs to be overcome by adding organic matter and nutrients needed to improve soil fertility as a growing medium for cauliflower plants. This study aims to determine the interaction of chicken manure as organic matter and NPK on the growth and yield of flower cabbage on alluvial soil. This research was conducted at Jalan Daya Nasional, Tanjungpura University Lecturer Complex, Pontianak from 27 December "“ 28 March 2022. This research is a field experiment with a factorial pattern of Completely Randomized Design (CRD) consisting of 2 factors. The first factor consisted of chicken manure (K) which consisted of 3 treatment levels and the second factor was NPK fertilizer (N) with 3 treatment levels. Each treatment combination was repeated 3 times and each experimental unit contained 4 sample plants, so there were 108 plants. The first factor is chicken manure which consists of 3 levels, namely: 108 ton/ha, 243 ton/ha and 378 ton/ha. The second factor is NPK fertilizer which consists of 3 levels, namely: 300 kg/ha, 450 kg/ha and 600 kg/ha. Observation variables include: number of leaves, root volume, dry weight of the top of the plant, fresh weight of flowers and flower diameter. The results showed that there was an interaction between chicken manure and NPK fertilizer on the variable number of leaves 4 WAP. The dose of 243 ton/ha and pupuk NPK 600 kg/ha fertilizer is an efficient dose to increase the growth of flower cabbage on alluvial soil. Keywords : Alluvial, Cabbage Flowers, NPK, Chicken Manure